Acoustic fields generation by plasmoids in the wellbores - Fedun, V.I.; Kolyada, Yu.E.; Bulanchuk, O.N. (Вопросы атомной науки и техники, 2013)
In this paper it is proposed a method of acoustic pulses generation in a wellbore by means a plasma gun which located at the well mouth. Acoustic measurements results are presented. It is shown that the wellhead pressure affects on the amplitude and hydrodynamic pulse shape, on its attenuation and the impact intensity at the wellbottom zone. It was determined the range of wellhead pressures at which a impulse force of wave reaches the highest values at the well bottom zone. It is shown that this method can favorably affect on the oil well productivity. У статті запропоновано метод генерації акустичних полів з використанням плазмової гармати. Наведено результати акустичних вимірювань. Показано, що тиск в усті свердловини впливає на амплітуду та форму гідроімпульсу, його загасання та на інтенсивність дії на область вибою. Визначено інтервал тисків в усті свердловини, при якому досягаються найбільші значення дії імпульсу сили на вибій. Показано, що даний метод може сприяти істотному збільшенню видобутку нафти. В статье предложен метод генерации акустических полей с помощью плазменной пушки. Приведены результаты акустических измерений. Показано, что давление на устье скважины влияет на амплитуду и форму гидроимпульса, его затухание и на интенсивность воздействия в области забоя скважины. Определен интервал давлений на устье скважины, на котором достигаются наибольшие значения импульса силы на забой скважины. Показано, что данный метод может благоприятно влиять на последующий процесс нефтедобычи.